Construction of Dead Shuttering Block Work in Cable Duct Bank - Srinivasan, Manikandan (International Journal of Scientific Research in Civil Engineering, 2022)
In modern day of construction industries, like many other methodological innovations, dead shuttering block work shoring has been used in constructions for underground basement across in all areas. Little research has been done to explore the dead shuttering block works at the future duct bank openings which is performed after completing the entire projects for underground services (Mechanical, Electrical and Plumping). This paper analyses about the two type of block work uses in basement wall, type 01 - Continues blockwork without an opening at duct banks and type 02 - Block works with opening at duct bank areas. As the deep foundations has inevitable concerns pertaining high water table, principle of demonstrating both type of block works justifies the materials requirements, methodology of water proofing, block works constructions and which type is suitable for successive implementation in current projects.